Teachers during Covid-19 in Terms of Academic Supervision and Work Life Balance - Wienda Gusta; Zahratul Azizah; Nurhizrah Gistituati; Rusdinal (CV. AFDIFAL MAJU BERKAH, 2022)
The purpose of the study was to test the effect of academic supervision and work life balance on teacher performance during Covid-19. This type of research is quantitative with an explanatory research approach. There were 92 teachers of SMK 8 Padang who were selected as samples in the study based on saturated sampling techniques. Research data collected through a questionnaire for academic supervision. The data was collected using questionnaires with a 5-point likert measurement scale. Findings in this study with regression analysis multiple linear showing the results of the analysis that: there is an influence of academic supervision on teacher performance during Covid-19 H1 received; there is a work life balance effect to the performance of teachers during Covid-19 H2 received; and there is an influence of academic supervision and work life balance simultaneously on teacher performance during Covid-19 H3 received.